2022
DOI: 10.1021/acsomega.2c04650
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photocatalytic Dye Degradation and Bacterial Inactivation by Graphitic Carbon Nitride and Starch-Doped Magnesium Hydroxide Nanostructures

Abstract: The removal of hazardous pollutants from water is becoming an increasingly interesting topic of research considering their impact on the environment and the ecosystem. This work was carried out to synthesize graphitic carbon nitride (g-C 3 N 4 ) and starch-doped magnesium hydroxide (g-C 3 N 4 /St-Mg(OH) 2 ) nanostructures via a facile co-precipitation process. The focus of this study is to treat polluted water and bactericidal behavior with a ternary system (doping-dependent Mg(OH) 2 ). Different concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This investigation (Figure c) indicated that the TOC of produced compounds under visible light irradiation decreased steadily with reaction time, and a considerable quantity of mineralization of dye was noticed after 150 min in Fe (6 wt %)-doped CdO. Moreover, results suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. , The comparison of the current work with the literature, in terms of photocatalytic activity and reaction time is shown in Table .…”
Section: Resultsmentioning
confidence: 55%
“…This investigation (Figure c) indicated that the TOC of produced compounds under visible light irradiation decreased steadily with reaction time, and a considerable quantity of mineralization of dye was noticed after 150 min in Fe (6 wt %)-doped CdO. Moreover, results suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. , The comparison of the current work with the literature, in terms of photocatalytic activity and reaction time is shown in Table .…”
Section: Resultsmentioning
confidence: 55%
“…The rate constant also depends on the different parameters of the photo reactor. 44 According to Selli et al (2000), photocatalytic degradation kinetics ( k ) was computed using the following pseudo-first-order kinetic equation 45 …”
Section: Resultsmentioning
confidence: 99%
“…This allowed us to calculate the rate constant represented in Figure 6a− suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. 65,66 The bactericidal effectiveness of bare Fe 2 O 3 , St/Fe 2 O 3 , and (2, 4 wt %) Sr/St-doped Fe 2 O 3 NSs was obtained from inhibition zone measurements via an agar-well diffusion assay for S. aureus (G +ve) and E. coli (G −ve) as mentioned in Table 2. Specific concentrations (1.0 mg/50 μL and 0.5 mg/50 μL) of bare and Sr/St-Fe 2 O 3 NSs were filled in concerning wells, and CF (0.05 mg/50 μL) was utilized as a positive control for the comparison; meanwhile, DI water (50 μL) was used as the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…This investigation (Figure ) indicated that the TOC of produced compounds under visible light irradiation decreased steadily with reaction time, and a considerable quantity of mineralization of dye was noticed after 180 min in Sr/St-Fe 2 O 3 (4%). Moreover, results suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation